Perencanaan Jumlah Pembelian Bahan Baku di CV. Prima Maju Jaya dengan Mempertimbangkan Fluktuasi Harga - Veronica Salim; Tanti Octavia (Jurnal Titra, 2016)
CV. Prima Maju Jaya is difficult to estimate the purchase number of raw materials since the chemical raw material prices are always fluctuating. This final assignment was conducted using the Continous Review concepts to know the ordering time before it runs out. Methods of special sale prices and known price increases used to determine how many items should be ordered. This research will assist the company in determining the quantity and the ordering time for minimizing the inventory costs. Alternative order quantity is represented by the lowest cost, the highest cost, and the average cost of the last two months. Alternative order quantity is compared with the company's condition. Cost of inventories of chemicals types A through G will be minimal when an alternative numbers is applied, except for the chemicals types B. Sensitivity analysis models Economic Order Quantity (EOQ) is also done to determine the impact of the parameter of ordering and holding costs.